2021
DOI: 10.1177/0031512521990352
|View full text |Cite
|
Sign up to set email alerts
|

Sex Does Not Sell: Effects of Sexual Advertising Parameters on Women Viewers’ Implicit and Explicit Recall of Ads and Brands

Abstract: This study investigated implicit and explicit memory effects of sexual and non-sexual advertisements embedded in either a sexual or non-sexual program among women viewers. We predicted that sexual appeals would facilitate implicit memory for the brand, and we explored whether program-type (sexual or non-sexual) and its associated congruity would impact or moderate recall of the surrounding advertisement among a small sample (n = 52) of exclusively women advertisement viewers. Sexual (versus non-sexual) adverti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
3
3
0
Order By: Relevance
“…In sum, our results in this study suggest that sex does not sell, a finding that is consistent with that of earlier studies (Bushman & Bonacci, 2002) and meta-analyses (Lull & Bushman, 2015). Sexual advertising did not lead to enhanced recognition memory for the commercials, and implicit memory was better for the nonsexual advertisements, confirming the findings from Lawrence et al, (2021) who similarly found that sexual advertising led to increased memory for the advertisement scene itself at the expense of recalling the brand.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In sum, our results in this study suggest that sex does not sell, a finding that is consistent with that of earlier studies (Bushman & Bonacci, 2002) and meta-analyses (Lull & Bushman, 2015). Sexual advertising did not lead to enhanced recognition memory for the commercials, and implicit memory was better for the nonsexual advertisements, confirming the findings from Lawrence et al, (2021) who similarly found that sexual advertising led to increased memory for the advertisement scene itself at the expense of recalling the brand.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of implicit memory superiority for nonsexual advertisements is in line with Lawrence et al (2021) in which logos and image degradation were used as an implicit memory measure. Moreover, Shapiro and Krishnan (2001) and Law and Braun-LaTour (2004) suggested that implicit memory measures are more ecologically valid and reflective of real-world consumer behavior than are explicit memory measures.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations